Monsoon Fringe Area Moisture Transportation Revealed by Water Stable Isotopes: A Lanzhou River Valley Case Study - Du, Jia; Liu, Jingfeng; Zhang, Mingjun (Frontiers in Environmental Science, 2022)
Because of global warming, the water cycle has intensified, and precipitation has changed, with monsoons evolving to become more complex, particularly in monsoon fringe areas. Therefore, it is important to use stable isotopes to trace moisture sources in monsoon fringe areas, such as semi-arid areas. In this study, in situ measurements of water vapour isotopes were obtained in the monsoon fringe area of Lanzhou, (36.1° N, 103.7° E), between May and November 2019 with the aim of analysing the stable isotope composition and atmospheric water vapour variation to improve our understanding of moisture transport. The following results were obtained: stable isotopic variation of atmospheric water vapour shows an alternation between west and southwest moisture with wind directions and sources of water vapour, with δ18O and δ2H varying from high to low. In the Lanzhou valley, water vapour isotopes show a distinct daily cycle of δ17O, δ18O, and δ2H and are consistent with temperature changes. Water vapour isotopes, particularly d-excess, are correlated with temperature and absolute humidity. With regard to the local atmospheric water vapour line (LAVL), we show that the slope and intercept of the LAVL are affected by sub-clouds secondary evaporation and topography.